Praktik Etika Bisnis dalam Tata Kelola Dana Simpan Pinjam Komunitas Perkotaan: (Studi Kualitatif : Kredit Macet di Wilayah Kelurahan Airlangga Kecamatan Gubeng Surabaya) - Siswohadi Siswohadi; Jajuk Susanto; Maratus Sholihah; Ratna Wati; Rosidi Rosidi; Adriyan Adriyan (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2026)
This study aims to analyze the implementation of business ethics in the governance of urban community savings and loan funds and its implications for non-performing loans in Airlangga Village, Gubeng District, Surabaya. Community-based savings and loan funds serve as an economic empowerment mechanism that relies on trust, responsibility, transparency, and accountability in their management. Nevertheless, loan default remains a significant challenge that may threaten program sustainability and weaken trust among members. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and document analysis involving fund administrators, borrowing members, and other relevant stakeholders. Data analysis was conducted through data reduction, data display, and thematic conclusion drawing. The findings reveal that business ethics principles have generally been integrated into the governance of community savings and loan funds, particularly in terms of honesty, responsibility, and deliberative decision-making. However, several challenges persist, including inadequate borrower eligibility assessment, low repayment discipline, and the influence of close social relationships that often reduce objectivity in lending decisions. These conditions contribute to the emergence of non-performing loans and create ethical dilemmas for administrators when carrying out collection activities and imposing sanctions. The study concludes that strengthening ethics-based governance is essential through improved transparency, consistent enforcement of regulations, and enhanced financial literacy among members. These findings provide practical insights for community savings and loan managers in developing more sustainable, accountable, and ethical financial management systems while maintaining the social values that underpin community-based financial institutions.